Characteristics, treatments, and outcomes of severe sepsis of 3195 ICU-treated adult patients throughout Japan during 2011–2013. Issue 1 (December 2016) - Hayakawa, Mineji; Saito, Shinjiro; Uchino, Shigehiko; Yamakawa, Kazuma; Kudo, Daisuke; Iizuka, Yusuke; Sanui, Masamitsu; Takimoto, Kohei; Mayumi, Toshihiko; Azuhata, Takeo; Ito, Fumihito; Yoshihiro, Shodai; et al.
Abstract Severe sepsis is a major concern in the intensive care unit (ICU), although there is very little epidemiological information regarding severe sepsis in Japan. This study evaluated 3195 patients with severe sepsis in 42 ICUs throughout Japan. The patients with severe sepsis had a mean age of 70 ± 15 years and a mean Acute Physiology and Chronic Health Evaluation II score of 23 ± 9. The estimated survival rates at 28 and 90 days after ICU admission were 73.6 and 56.3 %, respectively.